Beneficial Effects of Stinging Nettle Supplementation on Milk Production - Khanal, D.R.; Tiwari, I; Bastola, R.; Upreti, C.R. (Nepalese Veterinary Journal, 2017)
After having demonstrated the beneficial effects of stinging nettle supplementation in poultry and pigs, a month long on-station pilot trial in 10 lactating cattle of second to third stage of parity at Cattle Research Programme at Nepal Agricultural Research Council, Lalitpur was carried out. Daily supplementation of 20 gm nettle powder to dairy cattle resulted in enhanced milk production by 0.9 litres on an average compared to milk yield before nettle supplementation (3.2 litres/day versus 4.1 litres/day). After the on-station pilot trial; an on-farm trial in Tanahun, 150 km west of Kathmandu was carried out in 12 lactating Jersey cross cows by daily supplementation of 20 gm (T1) and 40 gm (T2) of nettle powder in two groups (n=4 cows/group) of cattle and productive performance was compared with control. Milk yield in terms of quantity and quality was recorded one week prior and during nettle supplementation. Qualitative analysis of milk samples was done every 14 days to measure levels of milk fat, solid non-fat and milk protein using Lactoscan. Available data on on-farm trial showed that there was increment in milk production in both treatment (T1 and T2) groups by 8.08% and 10.19%, respectively against control. Similarly, fat percentage was also increased compared to fat level prior to nettle supplementation in both T1 (3.52% vs. 4.15%) and T2 (3.46% vs. 4.46%) groups while in control group there was very negligible change (3.24% vs. 3.33%). Likewise, there were also remarkable increment in solid non-fat (SNF) and milk protein in nettle fed groups against control. Furthermore, overall body condition score in nettle supplemented group was better than that of control towards the end of supplementation. Our findings exhibited the beneficial effects of stinging nettle supplementation in enhancing the quantity and quality milk yield besides improving body condition score of the dairy cattle.